A wellbeing approach in social policies for tackling child poverty in Portugal - Souza, Tainna Paiva (2023)
Child poverty is a significant problem with far-reaching consequences, perpetuating cycles of poverty, social inequality and exclusion. The current monetary approach for measuring poverty does not consider important variables such as family structure, gender, age, discrimination, access to basic sanitation, school enrollment and nutrition. Therefore, adopting a focused approach that takes into account the diverse of dimensions of children lives that are essential to their overall wellbeing, is essential to produce effective policies for children in poverty. This research work investigate the current social policies to tackle child poverty in Portugal and proposes a multidimensional well-being approach to address the various dimensions of child poverty and promote a dignified quality of life. The objectives of the research were to investigate existing social policies to combat child poverty in Portugal and to determine which dimensions of child poverty they target, to analyze how these policies contribute to children's well-being and to propose a multidimensional well-being approach to increase the effectiveness of social policies in Portugal, using Bradshaw & Richardson's (2009) Child well-being dimensions as theoretical approach. To collect data, a literature review on theories of child poverty and well-being was carried out, together with an analysis of existing data on measures of child poverty in Portugal. Additionally, Problem-centred-interviews were conducted with experts in the field of social security and policy formulation in Portugal. The results revealed that current social policies in Portugal only partially address the dimensions of child well-being, and there is a heavy reliance on social protection units to individually navigate and meet the diverse needs of children within the social protection system, for which many gaps were found, such as the disparity of access of children to public policies like quality of health-care and education depending on the region they are located, and scarcity of professionals available to follow the cases. The research highlights the importance of a focused multidimensional well-being approach in social policy making to ensure comprehensive support for children living in poverty and the need to address the various dimensions of child poverty and promote their overall well-being. The results can inform policy development and decision-making processes to create more effective social policies to combat child poverty in Portugal.